Self-selection among undocumented immigrants from Mexico - Pia M. Orrenius; Madeline Zavodny (Federal Reserve Bank of Atlanta, 2001)
This paper examines the effect of changes in migration determinants on the skill level of undocumented immigrants from Mexico. The authors focus on the effect of changes in economic conditions, migrant networks, and border enforcement on the educational attainment of Mexican-born men who cross the border illegally. Although previous research indicates that illegal aliens from Mexico tend to be unskilled relative to U.S. natives and that economic conditions, networks, and border enforcement affect the size of illegal immigrant flows across the border, the interaction of these variables has not been investigated. Results from hazard models using data from the Mexican Migration Project indicate that improvements in U.S. and Mexican economic conditions are associated with a decline in the average educational levels of undocumented immigrants. Stricter border enforcement is associated with higher average skill levels. Access to a network of previous immigrants appears to lower the cost of migrating but has no differential effect by skill level.
Keywords: 330; Immigrants; Emigration and immigration; Labor supply